Perbedaan Media Tanam Limbah Kulit Buah Kolang Kaling dan Kulit Kopi terhadap Pertumbuhan Tanaman Begonia - Linna Fitriani; Reny Dwi Riastuti; Destien Atmi Arisandy (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the differences in the planting media of kolang kaling fruit peel waste and coffee skin on the height, number of leaves and leaf width of begonia plants. The method used in this research is a quantitative experimental method with two treatments of growing media, namely the waste of kolang kaling fruit peel and coffee rind waste. Data collection techniques using observation sheets. The results of observations on the growth of begonias were analyzed using independent t-test. The results showed that there was a difference in begonia plant height with the value of Sig. of 0.648. The number of begonia plant leaves obtained the value of Sig. by 0.007 and the width of the leaves of begonia plants by 0.309. In conclusion, there are differences in the use of planting media for waste skin of kolang kaling fruit and coffee husk waste planting media on the number of leaves on begonia plants. Keywords: Planting Media, Begonia Growth